Duties of Sub-District Head in Implementing Regional Autonomy Based on Law Number 23 of 2014 - Surya, Ida (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Since the enactment of Law Number 23 of 2014, the Sub-district Government has undergone many changes in line with the changing paradigm of government as mandated in Law Number 23 of 2014 concerning Regional Government. The purpose of the position and duties of the Sub-district Head in the Regional Autonomy era is to improve coordination of government administration, public services, implement development, and empower Village/Kelurahan communities. The method used is an empirical research method with a legislative study approach and a conceptual and sociological approach. The data analysis used is the method of interpretation of legislation and authentic interpretation, as well as field data. The expected result is that the Sub-district government is required to be sensitive to the changes that occur. All public services and civil services that were previously conventional are now required to be technology-based. The Sub-district Head, as the head of government at the Sub-district level, and other government units, including Village governments should collaborate and coordinate in all sectors.